EFEKTIVITAS KINERJA PENGELOLAAN RETRIBUSI PASAR DAN KONTRIBUSINYA TERHADAP PENERIMAAN RETRIBUSI DAERAH KABUPATEN SUMBAWA - Suprianto, S; Alwasifah, Yulistia (Pusat Riset dan Publikasi, 2024)
This study aims to determine the effectiveness and contribution of market retribution to regional retribution revenues in Sumbawa District. The type of this study was descriptif with a quantitative approach. The type of data used in this study was quantitative data obtained from secondary sources in the form of books, journals and reports contained in the Regional Financial and Asset Management Agency of Sumbawa District. The data collected in this study was analyzed using effectiveness, growth rate and contribution analysis techniques. The results of this study showed that 1) in general, the ratio of market retribution revenue in Sumbawa District for 2017-2021 was in the quite effective category. 2) in general, the growth rate ratio of regional retribution revenue in Sumbawa District for 2017-2021 was in the less successful category. and 3) in general, the ratio of contribution from market retribution to regional retribution in Sumbawa District for 2017-2021 was in the very good category. Therefore, optimal efforts are needed from the regional government to explore all the potential that exists in the market so that the results of collecting market retributions can be in accordance with the targets that have been set. The regional government is expected to be able to collect data on potential retribution in Sumbawa District so that the potential resulting from collecting regional retribution will be maximized and in line with the targets that have been set.